2006
DOI: 10.4049/jimmunol.177.5.2755
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Interleukin 4-Dependent Mast Cell Proliferation Requires Autocrine/Intracrine Cysteinyl Leukotriene-Induced Signaling

Abstract: Reactive mastocytosis (RM) in epithelial surfaces is a consistent Th2-associated feature of allergic disease. RM fails to develop in mice lacking leukotriene (LT) C4 synthase (LTC4S), which is required for cysteinyl leukotriene (cys-LT) production. We now report that IL-4, which induces LTC4S expression by mast cells (MCs), requires cys-LTs, the cys-LT type 1 receptor (CysLT1), and Gi proteins to promote MC proliferation. LTD4 (10–1000 nM) enhanced proliferation of human MCs in a CysLT1-dependent, pertussis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 28 publications
6
68
0
Order By: Relevance
“…In a separate study, exogenous LTD 4 induced the proliferation of hMCs by causing transactivation of c-Kit, the receptor for SCF, through CysLT 1 R (37), while CysLT 2 R counter-regulates these responses (35). Unexpectedly, despite its weak activity at CysLT 1 R and CysLT 2 R, LTE 4 increased the numbers of MCs arising from liquid culture of cord blood mononuclear cells more potently than LTC 4 or LTD 4 (37). We now report that LTE 4 signals though a distinct, MK571-sensitive pathway independent of CysLT 1 R and CysLT 2 R , , thereby linking extracellular LTE 4 to peroxisome proliferator-activated receptor ␥ (PPAR␥)-dependent ERK activation, inducible expression of COX-2, and generation of PGD 2 .…”
Section: ϫ8mentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study, exogenous LTD 4 induced the proliferation of hMCs by causing transactivation of c-Kit, the receptor for SCF, through CysLT 1 R (37), while CysLT 2 R counter-regulates these responses (35). Unexpectedly, despite its weak activity at CysLT 1 R and CysLT 2 R, LTE 4 increased the numbers of MCs arising from liquid culture of cord blood mononuclear cells more potently than LTC 4 or LTD 4 (37). We now report that LTE 4 signals though a distinct, MK571-sensitive pathway independent of CysLT 1 R and CysLT 2 R , , thereby linking extracellular LTE 4 to peroxisome proliferator-activated receptor ␥ (PPAR␥)-dependent ERK activation, inducible expression of COX-2, and generation of PGD 2 .…”
Section: ϫ8mentioning
confidence: 99%
“…LTE 4 -induced Changes in Phosphorylation of Signaling Intermediates-LTD 4 -mediated proliferation and cytokine generation by primary hMCs both require the phosphorylation of ERK (36,37). Because LTE 4 potently induced cytokine generation and proliferation, we analyzed the ability of LTD 4 and LTE 4 to induce phosphorylation of various signaling intermediates in the ERK pathway.…”
Section: Induction Of Chemokines and Cytokines By Cys-lts-ltcmentioning
confidence: 99%
“…IL-4, IL-5, and IL-13 augment CysLT production. IL-4 up-regulates LTC4 synthase and CysLT 1 receptor gene expression (10). LT synthase is induced by IL-13 in human lung macrophages (11).…”
mentioning
confidence: 99%
“…Mast cells are known to robustly produce cysteinyl LTs upon inflammatory stimulation and bear the cysteinyl LT receptors CysLT1 and CysLT2. The role of autocrine secretion of constitutively produced cysteinyl LTs in mast cell functions has been shown by using BMMCs grown in the presence of stem cell factor (SCF) and IL-4 (Jiang et al 2006). This previous study has shown that the genetic depletion of CysLT1 in BMMCs or treatment of BMMCs with MK571, a CysLT1 antagonist, markedly attenuates their proliferation with reduced phosphorylation of ERK1/2.…”
Section: Constitutive Cyslt1-mediated Signals Affect the Degranulatiomentioning
confidence: 99%
“…Cysteinyl LTs are released from leukocytes in the early phase of the inflammatory response and serve as contractile agonists for tissues that contain smooth muscles, such as blood vessels and bronchi. Besides their role as contractile agonists, cysteinyl LTs stimulate various cells and exert pleiotropic effects such as hematopoiesis, cellular migration (Bautz et al 2001), leukocyte adhesion to endothelial cells (Kanwar et al 1995;Pedersen et al 1997;Nagata et al 2002;Di Gennaro et al 2004), chemoattraction (Laitinen et al 1993;Spada et al 1994), cell proliferation, and cell survival (Jiang et al 2006;Vannella et al 2007;Bosse et al 2008). In the pathological context, cysteinyl LTs play important roles in the manifestation of allergic symptoms; therefore, receptor antagonists against cysteinyl LTs are widely used for anti-allergic therapy.…”
Section: Tohoku University Medical Pressmentioning
confidence: 99%